Linguistic Sign Oon The Meaning of Sikerei’s Wife’s Tattoos in Madobag Village, South Siberut Mentawai Island - Astuti, Amelia Yuli; Sakaliou, Tuiyak (Jurnal Ilmiah Langue and Parole, 2024)
This research is entitled "Linguistic Signs in the Meaning of Sikerei's Wife's Tattoos in Madobag Village, South Siberut, Mentawai Island. This research is limited to several main ideas related to the observation of the following two questions: What are the signs and markers of the meaning of the Sikerei wife's tattoo in Madobag, What are the provisions for marking the meaning of the Sikerei wife's tattoo in Madobag, The aim of this research is to find out the linguistic signs that used in the meaning of the Sikerei Wife tattoo. To explain the signs and markers in the meaning of the Sikerei Wife tattoo in Madobag. The theory used comes from Chandler and Barthes' semiotic theory which is used to answer the objectives of this research. For the data analysis method, the author uses qualitative research with the emphasis on inner meaning and understanding (verstehen), reasoning, definition of certain situations (in several contexts), studying things related to everyday life such as the culture of a region and also semiotic theory. Data collection techniques use literature study techniques to search for data that is relevant to the main analysis. This research is qualitative research using field notes, interviews, personal documents, and photos or drawings. The conclusion in this analysis is that the Sikerei Wife Tattoo for the Madobag community is part of the order of life based on Arat Sabulungan beliefs. This belief is a genuine religion and gives enthusiasm for life. Sikerei's wife's tattoo is one of the cultural heritages of the Mentawai people's ancestors. Sikerei's wife's tattoo pattern is a visual language as a means of communication to show the origin of existence, a sign of territorial ownership, and other symbols.